Developing Canva-Based Learning Media on Maps and Class Layout for Third Graders of Elementary School - Friendha Yuanta; Diyas Age Larasati (Universitas Nahdatul Ulama Surabaya, 2023)
This study aimed to develop Canva-Based Learning Media to produce feasible and effective learning media products on Maps and Class Layout for third graders at SDN Dukuh Kupang V Surabaya. The study used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected using a questionnaire instrument and analyzed through validity tests conducted by media experts, content experts, the target audience, and pre-tests and post-tests for students. The results showed that the animated media is categorized as appropriate, with validity results of 90% from media experts, 92,5% from content experts, and 91.25% from participant tests. Furthermore, the pre-test and post-test results showed an 8% improvement, signifying its effectiveness as a learning medium for third graders at SDN Dukuh Kupang V Surabaya.